Quality of Root Canal Fillings Performed by General Dental Practitioners in Libya: A radiographic assessment - Orafi, Ibtesam (Scientific Journal of University of Benghazi, 2020)
Aim: to evaluate radiographic quality of root canal fillings performed by General Dental Practitioners (GDPs) in Libya. Methods: A total of 599 endodontically treated teeth with 994 roots were evaluated. Assessment of the quality of root canal fillings was done by tracing digital periapical radiographs for different types of teeth without enhancement by two calibrated endodontists, evaluating length, density and taper. The length of each root canal filling was categorized as acceptable, short or overfilled based on the relationship of the filling with the radiographic apex. Density and taper were evaluated based on presence of voids and uniform tapering of the filling. The overall quality was considered adequate if all three criteria were adequate. Results: Overall 11.7% of all evaluated teeth had an acceptable root canal filling Adequate length of root filling was found in 53% of the maxillary teeth and in 40.4% of mandibular teeth. A significance difference (P<0.001) was found between tooth type and length of root canal filling (48.2%, 11.9% and 39.9% for adequate, over, and short root filling respectively). Adequate density was found in 22.3% of maxillary and 17.4% of mandibular teeth. A significant difference between tooth type and density of root filling (P<0.05) was found. Adequate taper was found also in 42% of maxillary and 33% of mandibular teeth. There was a significant difference (P<0.001) between tooth type and adequacy of root filling taper. Conclusion. The technical radiographic quality of root canal fillings performed by general dental practitioners was found to be substandard. There is an urgent need to improve it.